(untitled) (Nexo Revista Científica, 2020)
In today heat exchange applications, the plate heat exchanger (PHE) is quite used in chemical en food industries. At the present work the assessment of a PHE to carry out the cooling of an acetic acid stream, using ethylene glycol as refrigerant agent was accomplished. It was obtained a value of 29.34 % for the percent over surface design (OS), a heat exchanger effectiveness (ε) value of 0.667, a number of heat transfer units (NTU) value of 1.316, while the pressure drop results for both the acetic acid (6.70 kPa) and ethylene glycol (82.06 kPa) were below the maximum permissible limit for the process (100 kPa). The increment of the acetic acid feed flowrate increased the values of the three parameters considered, while the increment of the acetic acid inlet temperature augmented three of the variables taken into account, except for the acetic acid pressure drop, which was reduced. The proposed PHE can be satisfactorily used for the evaluated heat transfer process.